Development of an electronic system for the control, monitoring and follow-up of patients with neurodegenerative diseases through biomedical signal processing (2019)
The present work describes in a detailed way the process of design, implementation and testing of a control, monitoring and follow-up system for patients with neurodegenerative diseases. This system is a tool to provide peace of mind to people who have relatives with a neurodegenerative disease and who for several reasons must remain alone without the care of specialized personnel. The proposed system consists of an electronic prototype and a web service hosted in the internet cloud. The electronic prototype oversees and receives the information of a photo-plethysmography (PPG) sensor and an accelerometer, also manages the communication with the GPS module to obtain the geographical coordinates where the device is located and sends this coded information through an Access Point Name (APN) to the server. The server receives the frames, evaluates its validity and updates the web interface so that the client can see in real time the location and status of the heart rate and the level of oxygen saturation in the blood of the family being monitored. The web interface allows to see through two graphical indicators if there are abrupt changes in the cardiac rhythm and in the position of the patient (falls or strong blows).